The impact of corporate sustainable management activities on customer satisfaction and loyalty in the port sector : an empirical study on Singapore container port (PSA)’s non-shipping line users - Utami, Sylvia (2015)
With the vast growing popularity of sustainability activities, the port sectors have also been encouraged to integrate these activities in their business strategy. This report aims to fill the gap in evaluating the actual correlation and benefit arising from the implementation of Corporate Sustainable Management Activities (CSMA). The CSMA discussed in this report consists of three main pillars: Economic (EC), Social (SO) and Environment (EN). This main objective is to study the impact of CSMA on Customer Satisfaction (CS), Customer Loyalty (CL) and Company Reputation (CR). The main evaluation of objective in the report were constructed through five main hypotheses: H1 – there is a positive relationship between CS and CL in container port H2 – there is a positive relationship between CSMA and CS in container port H3 – there is a positive relationship between CSMA and CL in container port H4 – there is a positive relationship between CSMA and CR in container port H5 – there is a mediating effect of CS and CR on impact of CSMA on CL in container port. A comprehensive interview was conducted with port operator to study more on the current CSMA practices and their intentions. On another hand, survey questionnaire were sent out to port users to gather some insights on their perception and awareness of CSMA. These inputs were then compared and analyzed quantitatively using Regression Analysis to study the potential correlation and strength of relationship among CSMA, CS, CL and CR. The findings from the data analysis supported H1, H2, H3 and H4 in concluding that there is a positive correlation between CSMA, CS, CL and CR. However, the strength of the relationship is ranging from weak to moderate. Additionally, the social pillar has the most impact on all CS, CL and CR. It was also discovered that there were mediating effect from both CS and CR in explaining impact of CSMA to CL. However, due to the low response rate, the generalization of findings should be done with caution. Furthermore, the comparison across port sector (container and multi-purpose) were made to study the trend on those hypotheses tested. This report also discusses academic and managerial implications which offered more insights for further studies and a glimpse for port managers to make informed decision related to this topic. Keywords: Corporate Sustainable Management Activities, Customer Satisfaction, Customer Loyalty, Company Reputation, Container Port, Non-Shipping Lines Users.